Shared Type Integrated Learning Tools for Human Respiratory System Material and Vibration Concepts for Students at SMPN 1 South Bulango - Rahayu Nusi; Masra Latjompoh; Citron S. Payu (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to examine the feasibility of shared type integrated science learning tools based on aspects of validity, practicality and effectiveness. This research uses the type of Borg and Gall R&D development modified by Sugiyono (2017). Data collection techniques are by means of observation, questionnaires and tests. The results of the validity of learning tools (RPP, LKPD, TES) obtained an average of 95.6%, 92.4% and 95.3% in the very valid category. The students' response to the shared type of integrated science learning tools obtained a percentage of 92.9% in the very good category. The percentage of student activity achieved was 82.7% in the very good category. And student learning outcomes obtained an N-Gain of 0.63 with medium criteria. From the data obtained, it can be concluded that the integrated science learning device type, shared material on the human respiratory system and the concept of vibration, has met the criteria of being valid, practically effective, so it is suitable for use in science learning at school.